Tricycloquinazoline-based monolayer conjugated metal–organic frameworks as promising hydrogen storage media: A theoretical investigation - Meng, Zhaoshun; Li, Qingyu; Sun, Huilin; Wang, Yunhui; Li, Xing'ao (Green energy & environment, 2025)
The pursuit of sustainable energy has driven a significant interest in hydrogen (H2) as a clean fuel alternative. A critical challenge is the efficient storage of H2, which this study addresses by examining the potential of tricycloquinazoline-based monolayer metal–organic frameworks (MMOFs with the first “M” representing metal species). Using density functional theory, we optimized the structures of MMOFs and calculated H2 adsorption energies above the open metal sites, identifying ScMOF, TiMOF, NiMOF, and MgMOF for further validation of their thermodynamic stability via ab-initio molecular dynamics (AIMD) simulations. Force field parameters were fitted via the Morse potential, providing a solid foundation for subsequent grand canonical Monte Carlo simulations. These simulations revealed that the maximum of saturated excess gravimetric H2 uptake exceeds 14.16 wt% at 77 K, surpassing other reported MOFs, whether they possess open metal sites or not. At 298 K and 100 bar, both the planar and distorted structures derived from our AIMD simulations demonstrated comparable excess gravimetric H2 uptake within the range of 3.05 wt% to 3.94 wt%, once again outperforming other MOFs. Furthermore, lithium (Li) doping significantly enhanced the excess H2 uptake, with Li-TiMOF achieving an impressive 6.83 wt% at 298 K and 100 bar, exceeding the ultimate target set by the U.S. Department of Energy. The exceptional H2 adsorption capacities of these monolayer MOFs highlight their potential in H2 storage, contributing to the design of more efficient hydrogen storage materials and propelling the sustainable hydrogen economy forward. [Display omitted] •Density functional theory calculations were used to identify the optimal metal species for H2 adsorption in monolayer MOFs.•The thermodynamic stability of the studied monolayer MOFs at 298 K was assessed by ab-initio molecular dynamics simulations.•The force field parameters for the Morse potential were optimized based on the scanning results.•Grand canonical Monte Carlo simulations revealed that the studied MOFs achieve over 12.61 wt% H2 uptake at 77 K and 40 bar.•Li-doped TiMOF exhibited remarkable H2 uptake, surpassing the DOE target at 298 K and 100 bar or 233 K and 12 bar.